Electoral violence in Nigeria's fourth republic: implication for democratic development / Adekola Abdulazeez Alao - Abdulazeez Alao, Adekola (Universiti Teknologi MARA, 2021)
Elections have meaning for most people only in a democratic context, because they lead to the choice of decision makers. Elections are the litmus test of any democratic governance. Nigeria over the years had conducted a number of elections mostly characterised by violence. Thus, this attribute has hindered Nigerian democratic development and also has advert effect on the credibility of election results. It is against this backdrop that the paper attempts to examine Electoral Violence in Nigeria's Fourth Republic: Implication for Democratic Development. The paper adopts secondary source of data collection using all relevant documented materials to analyse the work. The paper presents the conceptual framework; examines and critically discusses the types of electoral violence in Nigeria's Fourth Republic; identifies and discusses the implication of electoral violence on democratic development in Nigeria. Therefore, it is then discovered that electoral violence occurs in three occasions, which are: Pre, during and post elections periods. Consequently, violence that characterised elections in Nigeria's fourth republic is a major obstacle to democratic development and Nigerian inability to conduct free, fair and credible election. The study prescribes a number of measures that should be taken to deepen and consolidate democratic governance in Nigeria.